Role of cellular, molecular and tumor microenvironment in hepatocellular carcinoma: Possible targets and future directions in the regorafenib era. Issue 7 (15th April 2020) - Juengpanich, Sarun; Topatana, Win; Lu, Chen; Staiculescu, Daniel; Li, Shijie; Cao, Jiasheng; Lin, Jiacheng; Hu, Jiahao; Chen, Mingyu; Chen, Jiang; Cai, Xiujun
Abstract : Hepatocellular carcinoma (HCC) remains as one of the major causes of cancer‐related mortality, despite the recent development of new therapeutic options. Regorafenib, an oral multikinase inhibitor, is the first systemic therapy that has a survival benefit for patients with advanced HCC that have a poor response to sorafenib. Even though regorafenib has been approved by the FDA, the clinical trial for regorafenib treatment does not show significant improvement in overall survival. The impaired efficacy of regorafenib caused by various resistance mechanisms, including epithelial–mesenchymal transitions, inflammation, angiogenesis, hypoxia, oxidative stress, fibrosis and autophagy, still needs to be resolved. In this review, we provide insight on regorafenib microenvironmental, molecular and cellular mechanisms and interactions in HCC treatment. The aim of this review is to help physicians select patients that would obtain the maximal benefits from regorafenib in HCC therapy.